Development of a Web-Based Journal Information System for Daily Teaching and Learning Activities at SMAN 1 Payung - Marinda, Dina; Hermawan, Hardika Dwi (Universitas Muhammadiyah Surakarta, 2023)
This study aims to examine the quality of the information system for website-based class daily journals which were developed in the context of digitizing subject teacher journals at SMAN 1 Payung. The purpose of this research is to change the process of processing learning data into a computational system to make it more effective and efficient. The sample in this study were subject teachers who were randomly selected. This study uses the SDLC approach with the waterfall development method. Information system testing in research was carried out using the ISO 9126 testing model. Information system quality testing uses ISO 9126 testing standards in two aspects, namely usability and functionality. Usability data analysis was tested using the Computer System Usability Questionnaires (CSUQ) questionnaire using the Likert Scale as a measurement scale with the questionnaire instrument: Psychometric evaluation and instructions for use developed by IBM as a standard for measuring software in the usability aspect with a score of percentage. While data analysis on the functionality aspect was tested using the Guttman scale based on ISO/IEC 9126 calculation standards. Each instrument that has a value of